Outcomes of Opioid-Free Pathways Post-Ureteroscopy: Joint Analysis From Two Academic Centers - Awad, Mohannad A.; Assmus, Mark A.; Berg, Adrian N.; Lee, Matthew S.; Hallgarth, Luke A.; Krambeck, Amy E.; Sternberg, Kevan M. (Frontiers in Urology, 2022)
Objective: To combat alarming postoperative opioid prescribing in the United States (U.S.), many surgical specialties implement pathways to limit routine use of opioids with the goal of zero opioid prescribing. We sought to examine outcomes after implementing non-opioid post ureteroscopy (URS) pathways at two academic centers in the U.S. Materials & Methods: We examined patients who underwent URS utilizing a non-opioid postoperative pathway from November 1, 2016 – March 31, 2020. Primary outcomes included adverse events (Emergency Department (ED) presentation, and office phone calls for postoperative genitourinary symptoms). Results: In total, 699 patients underwent URS with stent placement. Of these, 652 (89.4%) were discharged without opioids and 74 (10.6%) received opioids. Of those discharged without opioids, 484 (77.4%) received non-steroidal anti-inflammatory medications. Compared to patients discharged without opioids, patients prescribed opioids were more likely to present to the ED (67 (10.7%) vs 14 (19.9%), p=0.037) and call the clinic (102 (16.3%) vs 22 (29.7%), p=0.004). In a multivariate analysis, patients prescribed opioids post URS (OR 1.9, 95% CI 1.1 – 3.5, p=0.024) and patients who had an opioid prescription preop (OR 2.2, 95% CI 1.1 – 4.5, p=0.032) were associated with higher odds of calling the clinic. Older patients (OR 0.98, 95% CI 0.97 – 0.99, p=0.006) were less likely to call. Conclusions: The study highlights almost 90% of patients can be discharged safely without opioids following URS. In our cohort, patients prescribed opioids experienced higher postoperative healthcare interactions. We hope our results encourage consideration of non-opioid pathways.